Improving the heat transfer characteristics of a Spiky Central Receiver Air Pre-heater (SCRAP) using helically swirled fins - Grobbelaar, Dewald (Stellenbosch : Stellenbosch University, 2019)
Thesis (MEng)--Stellenbosch University, 2019.